The design and analysis of a reconfigurable flight control system for advanced civil aircraft - Oliva, A. P. (Cranfield University, 1994)
This work is concerned with the design of a pitch-rate-commandattitude-hold Command and Stability Augmentation System in order that the augmented aircraft meets the Gibson dropback criterion, the Gibson phase-rate criterion and MIL-F—8785C requirements. The work shows two methods of design, pole-placement and optimal control, and discusses the design procedures, the advantages and disadvantages of each method. The work is also concerned with the redundancy aspect of the control law design, and so not only a sensor based design but also an observer-based design are investigated. In order to design the observer-based control law, a Doyle-Stein observer was implemented. Two methods showing how to design the observer are discussed and presented, and the special characteristics of this kind of observer are also considered. The performance of the observer-based control law was compared with that of the sensor-based control law. The failure transients and characteristics of the control law are also studied and presented. Finally an evaluation of the control law was carried out with a non-linear model of the B-747 aircraft, and a simple altitude-hold autopilot was designed to work together with the stability augmentation control law.